Melding Sociology and Economics: James Coleman's Foundations of Social Theory* - Frank, Robert H. (Journal of Economic Literature, 2015)
JHEN PUBLISHERS receive copies of reviews of their books, they quickly scan them for possible quotes for use in promotional materials. They are often frustrated to discover that a reviewer really liked the book, yet never managed to say so in a clear, unequivocal way. The people at Harvard University Press will experience no such frustration with this essay on James Coleman's application of rational choice theory to the classical issues of sociology. Professor Coleman's Foundations of Social Theory is a masterwork. Epic in scope, it is clear, engaging, and forcefully argued. Traditional sociologists will be unable to ignore its bold new agenda for their discipline. And the book will have a lasting impact on economics, political science, psychology, and other disciplines concerned with human behavior. Having issued this ringing endorsement of the work as a whole, I hasten to add that there are many points on which I find myself in substantial disagreement with Coleman. On some occasions, he pushes the rational choice theory too far; on others, not nearly far enough. But one of his great virtues is his remarkable willingness to articulate clear theories and commit himself to their predictions. In the process, he leaves himself open to being proved wrong, and indeed he sometimes is wrong. Yet how much more satisfying is his approach than the familiar alternative of constructing vague ad hoc explanations to fit known fact patterns. Foundations of Social Theory is organized into five parts. Part I, Elementary Actions and Relations, introduces the basic building blocks of the theory-actors, resources, interests, individual rights, and relatonships involving authority and trust. Part II's focus is the micro-tomacro transition; it applies the theory of rational individual behavior to the units developed in Part I to deduce how systems of actors will behave. Here, Coleman is concerned with social exchange, crowd behavior, and the emergence of social norms. In Part III, Coleman constructs a theory in which the principal actor is not the individual but the corporation. His aim is to explain how and why individuals empower formal organizations to act on their behalf, and the means whereby such authority can be revoked. Part IV, entitled Modern Society, employs the theories developed earlier to shed light on developments in contemporary social and economic life. Coleman devotes Part * James S. Coleman. Foundations of Social Theory. Cambridge, Mass. and London: Harvard University Press, Belknap Press, 1990. Pp. xvi, 993. ISBN 0-674-312250-2.